Association between two common SNPs, rs6564851 and rs6420424, and lutein and zeaxanthin levels in a cohort of US postmenopausal women with a family history of breast cancer - Von Holle, Ann; Shi, Min; O'Brien, Katie M.; Weinberg, Clarice R.; Sandler, Dale P.; Park, Yong-Moon Mark (Frontiers in Nutrition, 2024)
A better understanding of the factors contributing to systemic concentrations of carotenoids is necessary given the weak correlations between circulating levels and dietary intake of carotenoids. Although genetic variation may play a key role in the interindividual variability in carotenoid concentrations, few genome-wide association studies (GWAS) have focused on carotenoids.We used a random sample (n=519) of postmenopausal participants in the Sister Study with data on genotypes and plasma carotenoid levels to conduct GWAS for each of five carotenoids (mcg/mL): alpha-carotene, beta-carotene, cryptoxanthin, lycopene, and lutein/zeaxanthin. We used linear regression models and an additive genetic model to evaluate associations between 530,000 variants and inverse normal transformed carotenoid concentrations.We found evidence for one genome-wide statistically significant association with the combined carotenoids of lutein and zeaxanthin for the rs6564851-C (beta=-0.377, se=0.059, p=4.6x10 -10 ) and rs6420424-A (beta = -0.334, se=0.059, p=2.2X10 -8 , upstream of the beta-carotene oxygenase 1 (BCO1) gene on chromosome 16. No other variant was associated with any of the remaining four carotenoids.Our results for the common rs6564851 and rs6420424 variants correspond to previous findings. Although biologic mechanisms explain the association between beta-carotene and this variant, the inverse association with lutein/zeaxanthin will require further investigation.